Pure gold saturable absorber for generating Q-switching pulses at 2 µm in Thulium-doped fiber laser cavity - Muhammad, Ahmad Razif; Zakaria, Rozalina; Ahmad, Muhammad Taufiq; Wang, Pengfei; Harun, Sulaiman Wadi (Elsevier, 2019)
We experimentally demonstrate Q-switched Thulium-doped fiber laser operating at 1949.19 nm using pure gold saturable absorber (Au-SA) as a Q-switcher. The Au-SA was fabricated by depositing gold particles molecules using electron beam evaporation on the surface of a polyvinyl alcohol (PVA) film. Subsequently, stable Q-switched pulses were obtained within the 1552 nm pump power range from 343.1 to 467.3 mW, with repetition rate tuned from 11.7 kHz to 21.95 kHz. At 467.3 mW pump power, the TDFL produced pulses train with the pulse width of 2.6 μs and the maximum pulse energy of 89.8 nJ. These results propose that pure gold could be a promising saturable absorber for pulse generation in 2 µm wavelength region. © 2019